2021
DOI: 10.1103/physrevlett.126.011103
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Induced Scalarized Black Holes

Abstract: It was recently shown that a scalar field suitably coupled to the Gauss-Bonnet invariant G can undergo a spin-induced linear tachyonic instability near a Kerr black hole. This instability appears only once the dimensionless spin j is sufficiently large, that is, j 0.5. A tachyonic instability is the hallmark of spontaneous scalarization. Focusing, for illustrative purposes, on a class of theories that do exhibit this instability, we show that stationary, rotating black hole solutions do indeed have scalar hair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(99 citation statements)
references
References 60 publications
1
98
0
Order By: Relevance
“…[18] suffices to show that the onset of scalarization is determined entirely by the coupling with G. Interestingly, it has also been showed that black hole scalarization can be triggered by rapid rotation as well [24] and some corresponding scalarized black hole solutions have been found in Refs. [25,26]. In this scenario the threshold is still controlled by G; however, the critical contribution does not come from the mass of the black hole, but from the spin.…”
Section: Introductionmentioning
confidence: 96%
“…[18] suffices to show that the onset of scalarization is determined entirely by the coupling with G. Interestingly, it has also been showed that black hole scalarization can be triggered by rapid rotation as well [24] and some corresponding scalarized black hole solutions have been found in Refs. [25,26]. In this scenario the threshold is still controlled by G; however, the critical contribution does not come from the mass of the black hole, but from the spin.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, the phenomenon of spontaneous scalarization has been studied in the extended scalar-tensor-Gauss-Bonnet (eSTGB) gravity [16][17][18][19][20][21][22]. In particular, asymptotically antide Sitter (AdS) scalarized black holes, as well as their applications to holographic phase transitions, have been studied in a scalar-tensor model with non-minimally coupling the scaler field to the Ricci scalar and the Gauss-Bonnet term [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the spontaneous scalarization in f(R) gravity theories in the presence of a scalar field minimally coupled to gravity with a self-interacting potential was discussed in [62]. Also in ESGB theory the spin-induced black hole spontaneous scalarization, which is the outcome of linear tachyonic instability triggered by rapid rotation, was explored in [63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%